Security of property rights for whom? - Terra Lawson-Remer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Recent research regarding property rights and economic development often treats property rights security in a country as homogeneous, although protecting the private entitlements of some can entail preventing others from claiming and controlling those same resources. This one-dimensional conception of property rights ignores the significant variation in the risk of expropriation faced by different groups in the same country. Using a new set of indicators that measures the property insecurity of ethnocultural minorities, this study finds that in many countries members of marginalized groups face significantly higher property insecurity than foreign investors and domestic elites, and that although secure property rights for elites and foreign investors may be positively related to long-run development, property rights for marginalized groups are not.
Keywords: B0; K0; O10; 330; property rights; growth; minority groups; law; Eigentumsrecht; Entwicklung; Minderheit